Malthusian Trajectory for Heart Failure and Novel Translational Ambulatory Technologies - Niranjan, Bidargaddi; de Courten, Maximilian P.; Iyngkaran, Pupalan; Battersby, Malcolm (Current Cardiology Reviews, 2023)
Introduction: It has been estimated that congestive heart failure (CHF) will reach epidemic proportions and contribute to large unsustainable impacts on health budgets for any cardiovascular condition. Against other major trends in cardiovascular outcomes, readmission and disease burden continue to rise as the demographics shift. Methods: The rise in heart failure with preserved ejection fraction (HFpEF) among elderly women will present new challenges. Gold standard care delivers sustainable and cost-effective health improvements using organised care programs. When coordinated with large hospitals, this can be replicated universally. Results: A gradient of outcomes and ambulatory care needs to be shifted from established institutions and shared with clients and community health services, being a sizeable proportion of CHF care. Conclusion: In this review, we explore health technologies as an emerging opportunity to address gaps in CHF management.
Keywords: health